2005
DOI: 10.1002/app.22626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical confinement (< 125 nm) on the curing behavior of phenolic resin

Abstract: How the physical confinement of phenolic resin in nano porous silica (8 nm Յ pore diameter (D p ) Յ 125 nm) affected the polymer's curing behavior was examined by conducting differential scanning calorimetry experiments at 320 K Յ T Յ500 K. Our results suggested that upon incorporating the phenolic resin into the silica, its curing temperature was lowered. However, what was interesting was that there was an inverse linear dependence between the pore size and the curing temperature, i.e., the smaller the pore d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Simon et al reported that the rate of cure of bisphenol M dicyanate ester accelerated with decreasing pore diameter. ,, The enhanced reactivity and lower curing temperature was attributed to an increased number of collisions between monomers in the vicinity of the substrate. In contrast, Amanuel and Malhotra reported that the curing temperature of phenolic resin in porous silica increased with decreasing pore diameter . The higher curing temperatures were attributed to a loss of entropy induced by physical confinement; to compensate, curing temperature increased.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Simon et al reported that the rate of cure of bisphenol M dicyanate ester accelerated with decreasing pore diameter. ,, The enhanced reactivity and lower curing temperature was attributed to an increased number of collisions between monomers in the vicinity of the substrate. In contrast, Amanuel and Malhotra reported that the curing temperature of phenolic resin in porous silica increased with decreasing pore diameter . The higher curing temperatures were attributed to a loss of entropy induced by physical confinement; to compensate, curing temperature increased.…”
Section: Introductionmentioning
confidence: 88%
“…In contrast, Amanuel and Malhotra reported that the curing temperature of phenolic resin in porous silica increased with decreasing pore diameter. 40 The higher curing temperatures were attributed to a loss of entropy induced by physical confinement; to compensate, curing temperature increased. These conflicting reports highlight that the curing behavior of polymers in confined geometries may be dependent on many factors such as supporting substrate, type of polymer, and surface treatment, apart from just film thickness or pore diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The mean size of the clusters arising during the polymerization equals to hnðtÞi ¼ 2 1:5 À 2 ln ð1:5Þ À kðt À t 1 Þ À exp ½ À 2kðt À t 1 Þ=12 ¼ 2 1:5 À ln ð9=8Þ À kt t . t 1 (18) and increases indefinitely at time t 2 which is determined by the following condition kt 2 z 1.5 À ln (9/8) z 1.38 (19) Note that t 2 is the upper estimation and in reality the unlimited growth of cluster sizes starts a little earlier.…”
Section: Theoretical Model Of Size-dependent Polymerization Kineticsmentioning
confidence: 99%
“…Similar results were obtained earlier by Amanuel and Malhotra who have studied the effect of confinement on the curing behavior of phenolic resin confined in the nanopores of porous silica substrate. 19…”
Section: Introductionmentioning
confidence: 99%
“…However, the increase in the neat resin mechanical properties is by far smaller than the expected values. [11][12][13][14][15][16] For an effective reinforcement it is necessary to have a good dispersion, alignment, and good interfacial stress transfer between the reinforcement and matrix. The dispersion of individual CNTs in a matrix is probably the fundamental issue because it is desirable for efficient load transfer between the CNT network and the host matrix.…”
Section: Introductionmentioning
confidence: 99%